The application of multiple intelligences in the development of biology learning materials: A literature review - Mahmudah, Rif'atul; Wardani, Alinda Yulia; Irmawati, Irmawati; Tauhidah, Tauhidah; Alfatiha, Winada (UNIVERSITAS LAMBUNG MANGKURAT, 2026)
The need for Biology learning materials that can accommodate the diverse intelligences of learners has driven the growing use of the Multiple Intelligences approach in instructional material development. However, no systematic review has yet mapped how Multiple Intelligences are actually implemented in the development of Biology learning materials, nor the extent to which the different intelligences are integrated. This study employs a Systematic Literature Review (SLR) using the PRISMA model to analyze the application of Multiple Intelligences in Biology learning materials based on ten selected articles from 696 identified publications. The review findings show that various Multiple Intelligences–based products, such as e-books, flipbooks, modules, and e-worksheets, demonstrate strong validity, practicality, and effectiveness in improving conceptual understanding, learning motivation, critical thinking skills, and student engagement. Nevertheless, the implementation of Multiple Intelligences in most studies remains partial, as only a few intelligences are typically adopted, and only one article fully applies all nine intelligences comprehensively and contextually. The main contribution of this review lies in identifying this gap and mapping the patterns of Multiple Intelligences implementation in the development of Biology learning materials, a focus which has not been addressed in previous studies. Furthermore, this study highlights the lack of long-term evaluation and the limited exploration of affective aspects, thus offering important directions for future research.Abstrak. Kebutuhan akan bahan ajar Biologi yang mampu mengakomodasi keragaman kecerdasan peserta didik mendorong berkembangnya penggunaan pendekatan Multiple Intelligences (MI) dalam pengembangan bahan ajar. Namun, sejauh ini belum ada kajian sistematis yang memetakan bagaimana MI benar-benar diterapkan dalam pengembangan bahan ajar Biologi, termasuk sejauh mana kecerdasan-kecerdasan MI diintegrasikan. Penelitian ini menggunakan metode Systematic Literature Review (SLR) dengan model PRISMA untuk menganalisis penerapan MI pada bahan ajar Biologi berdasarkan 10 artikel terpilih dari 696 publikasi yang diidentifikasi. Hasil telaah menunjukkan bahwa berbagai produk seperti e-book, flipbook, modul, dan E-LKPD berbasis MI menunjukkan hasil yang valid, praktis, dan efektif dalam meningkatkan pemahaman konsep, motivasi belajar, kemampuan berpikir kritis, dan keterlibatan peserta didik. Meskipun, implementasi MI pada sebagian besar penelitian masih bersifat parsial karena hanya mengadopsi beberapa kecerdasan, dengan hanya satu artikel yang menerapkan sembilan kecerdasan secara komprehensif dan kontekstual. Kontribusi utama kajian ini terletak pada identifikasi kesenjangan tersebut serta pemetaan pola implementasi MI dalam pengembangan bahan ajar Biologi, yang belum dijelaskan dalam kajian sebelumnya. Selain itu, penelitian ini menyoroti kurangnya evaluasi jangka panjang dan minimnya eksplorasi aspek afektif, sehingga menjadi arah penting bagi pengembangan penelitian selanjutnya.